2005
DOI: 10.2166/wh.2005.0006
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and correlations between coliphages and anthropogenic viruses in the Massachusetts Bay using enrichment and ICC-nPCR

Abstract: We evaluated a two-step enrichment procedure to detect coliphages and an integrated cell culture-nested polymerase chain reaction (ICC-nPCR) to detect human astrovirus, enteroviruses, rotavirus and adenovirus type 40 and 41 in marine water samples collected by the Massachusetts Water Resource Authority (MWRA). MWRA has been monitoring its receiving waters for coliphages, anthropogenic viruses and indicator bacteria in order to evaluate the impact of Boston's Deer Island Sewage Treatment Plant discharge. Coliph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…In contrast, other studies have shown some correlation between human viruses and F-specific phages [23,123,126,140,141] and between human viruses and somatic coliphages in surface waters [104,140,142], between enteroviruses and somatic coliphages in sludge [82], and between human viruses and both somatic and F-specific phages in surface water [78]. Thus, even if the results far from indicate a clear correlation between indicator coliphage densities and human viruses in water, there is evidence that somatic and F-specific coliphages are more strongly associated with pathogenic viruses than the traditional bacterial indicators and even a particular pathogenic virus.…”
Section: Relationship To Human Virusesmentioning
confidence: 76%
“…In contrast, other studies have shown some correlation between human viruses and F-specific phages [23,123,126,140,141] and between human viruses and somatic coliphages in surface waters [104,140,142], between enteroviruses and somatic coliphages in sludge [82], and between human viruses and both somatic and F-specific phages in surface water [78]. Thus, even if the results far from indicate a clear correlation between indicator coliphage densities and human viruses in water, there is evidence that somatic and F-specific coliphages are more strongly associated with pathogenic viruses than the traditional bacterial indicators and even a particular pathogenic virus.…”
Section: Relationship To Human Virusesmentioning
confidence: 76%
“…In the absence of significant fecal pollution inputs, the levels of F-specific coliphage may be well below the limit of detection. In such cases, perhaps an enrichment method for the detection of F-specific coliphages would provide more valuable information than direct enumeration (87). When Ballester et al retested archived seawater sample concentrates prepared from large volumes (Ͼ100 liters of water) for the presence of coliphages, the rate of detection increased from 8% to 58% using a two-step enrichment method (87).…”
Section: Detection and Densities Of F-specific Coliphage And Viruses mentioning
confidence: 99%
“…In such cases, perhaps an enrichment method for the detection of F-specific coliphages would provide more valuable information than direct enumeration (87). When Ballester et al retested archived seawater sample concentrates prepared from large volumes (Ͼ100 liters of water) for the presence of coliphages, the rate of detection increased from 8% to 58% using a two-step enrichment method (87). However, with respect to sampling and laboratory management, processing larger volumes of water can be logistically cumbersome and would preclude, potentially, the identification of viral contamination in surface waters captured via the smaller-volume approaches defined in the current study, where over 1,150 samples from 24 surface water sampling sites were processed and analyzed.…”
Section: Detection and Densities Of F-specific Coliphage And Viruses mentioning
confidence: 99%
“…Some authors have suggested the use of an enrichment method because of a significant correlation between somatic coliphages, total enteric viruses, and adenoviruses (11). Others proposed the use of one bacterial indicator and somatic coliphages, which could be more informative than two bacterial indicators (22,29), and the observation of somatic coliphage replication must not be argued as a limitation (27).…”
Section: Discussionmentioning
confidence: 99%
“…Marine viruses were first described by Spencer (43), though they were largely ignored for 3 decades because of the relatively low abundances inferred on the basis of culturebased assays (12). However, more recently, it has been recognized that viruses are extremely abundant in aquatic environments (11,17,40,46,47). The viruses may exceed the concentration of bacteria by up to 100 times, with their total numbers estimated to be 10 31 in the biosphere (12).…”
mentioning
confidence: 99%